Evaluating the Impact of the Revised Special Supplemental Nutrition Program for Women, Infants, and Children Fruit Juice Allotment on Fruit Intake, Dietary Quality, and Energy/Nutrient Intakes among Children 1-4 Years of Age - Nicklas, T.A.; O’Neil, C.E.; III, V.L. Fulgoni (International Journal of Child Health and Nutrition, 2018)
Objective: The goals of this study were to assess the impact of recent changes in the WIC allotment on fruit intake, dietary quality/adequacy, energy/nutrient intakes, and potential impact of the complete removal of 100% fruit juice (FJ) from the package. Methods: 24-hour recalls from children 1-4 years who were WIC participants or income-eligible nonparticipants in the NHANES 2007-2008 and 2011-2014 (before and after WIC package changes) were analyzed. Results: There were no differences in the Healthy Eating Index-2015 total score; subcomponent scores for “greens and beans” and for “fatty acid ratio” were higher in 2011-2014 than in 2007-2008 in children participating in WIC; scores for “sodium” were higher in 2011-2014 than in 2007-2008 in children not participating in WIC but income-eligible. In WIC participants mean intakes of riboflavin, vitamins B12 and C, and zinc were significantly (p<0.01) lower, and intake of vitamin E was significantly (p<0.01) higher in 2011-2014 compared to 2007-2008. One significant difference in nutrient adequacy in children was that of a lower (p<0.01) percentage of inadequacy for WIC participants for vitamin E and a higher (p<0.01) percentage of inadequacy for WIC participants for vitamin A in 2011-2014 as compared to those in 2007-2008. The elimination of FJ from the WIC food packages resulted in a 38-50% lower total fruit intake and a 4-5% reduction in total HEI-2015 score. Conclusion: Changes in the WIC program resulted in potential adverse effects on mean intakes of some nutrients but not on the nutrient adequacy or overall diet quality. Confirmatory studies are needed.